2018
DOI: 10.1016/j.eurpsy.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter gene polymorphism as a predictor of short-term risk of suicide reattempts

Abstract: The 5-HTTLPR polymorphisms predicted short-term risk of suicidal reattempt independently of age and sex. L-carriers have almost three times more risk of relapse when compared with SS carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…Patients with low-expression 5HTTLPR genotypes and childhood trauma have an increased risk of suicidal behavior [63]. Some studies support an increased risk of suicide attempts in depressed patients with the S allele [64][65][66], though other studies have not found this association [67][68][69][70][71]. Sarmiento-Hernández et al [20] conclude that the higher S allele frequency in the studied population reinforces the hypothesis that the 5HTTLPR variants play an essential role in the development of suicidal behavior in depressed adolescents, regardless of the presence of another psychiatric comorbidity [20].…”
Section: Httlpr Variant and Mdd Risk Factorsmentioning
confidence: 99%
“…Patients with low-expression 5HTTLPR genotypes and childhood trauma have an increased risk of suicidal behavior [63]. Some studies support an increased risk of suicide attempts in depressed patients with the S allele [64][65][66], though other studies have not found this association [67][68][69][70][71]. Sarmiento-Hernández et al [20] conclude that the higher S allele frequency in the studied population reinforces the hypothesis that the 5HTTLPR variants play an essential role in the development of suicidal behavior in depressed adolescents, regardless of the presence of another psychiatric comorbidity [20].…”
Section: Httlpr Variant and Mdd Risk Factorsmentioning
confidence: 99%
“…Likewise, postmortem brain tissue biochemical analysis has shown a reduction of SERT in the frontal cortex, hippocampus, and putamen; however, contradictory outcomes have been observed depending on the brain region analyzed ( Purselle and Nemeroff, 2003 ; Steinberg et al., 2019 ). Besides, polymorphism at the transporter gene, particularly the polymorphism 5-HTTLPR predicts a three times higher-risk suicide compared to other alleles independent of age and sex ( Daray et al., 2018 ; Nielsen et al., 2019 ; Sarmiento-Hernández et al., 2019 ).…”
Section: Neurochemical and Neurobiological Findings Suicidal Behaviormentioning
confidence: 99%
“…Previous studies published contradictory findings, with some reporting females to be at increased risk for suicide after discharge [4,14,15], whereas others found males to be at an increased risk [3]. When investigating recurrent suicidal behavior, no significant sex difference was reported [16]. Further, previous studies were based on national or regional register data from single countries only.…”
Section: Introductionmentioning
confidence: 96%